Program PERMATA BUNDA sebagai Upaya Pencegahan dan Penurunan Stunting di Kabupaten Barito Kuala - Candra Wijaya (Jurnal Pengabdian Masyarakat Panacea, 2023)
Stunting merupakan masalah kesehatan yang berkaitan dengan peningkatan risiko keluhan, kematian serta hambatan pada masa pertumbuhan baik itu dari motorik maupun mental. program PERMATA BUNDA (Pemberian Makanan Tambahan Bagi Ibu Hamil dan Anak Balita) adalah salah satu upaya pemenuhan zat gizi spesifik dalam rangka mendukung 1000 Hari Pertama Kehidupan dan pemenuhan Standar Pelayanan Minimal Bidang Kesehatan, terutama untuk ibu hamil, bayi dan balita, serta mendorong terwujudnya generasi Barito Kuala yang tumbuh sehat dan bebas stunting. Hasil yang didapatkan dari implementasi PERMATA BUNDA dibutuhkan komitmen dan dukungan dari pemangku kebijakan, agar kebersinambungan manfaatnya dapat terus dirasakan masayarakat, karena Program PERMATA BUNDA terbukti dapat menurunkan kasus stunting di Barito Kuala, yaitu 16,86% pada tahun 2020 menjadi 12,56% pada tahun 2022 berdasarkan data ePPBGM tahun 2022. Kata Kunci: Permata Bunda; Stunting; Barito Kuala Stunting is a health problem associated with an increased risk of complaints, death, and obstacles during the growth period, both motor and mental. The PERMATA BUNDA program (Providing Supplementary Food for Pregnant Women and Toddlers) is one of the efforts to meet specific nutrition needs in order to support the First 1000 Days of Life and meet Minimum Service Standards in the Health Sector, particularly for pregnant women, infants, and toddlers, as well as encourage the creation of a new generation of Barito Kuala that are growing healthy and free of stunting. The Permata Bunda program is funded through budget synergy from the Village Community Empowerment Service for making ready-to-eat food menus for non-Chronic Energy Deficiency (KEK) pregnant women and undernourished toddlers, while for pregnant women and toddlers with KEK, the budget source is Health Operational Costs at the Health Center. The implementation of PERMATA BUNDA requires commitment and support from stakeholders, so that the benefits can continue to be felt by the community, because the PERMATA BUNDA Program has been proven to be able to reduce stunting cases in Barito Kuala, namely from 16.86% in 2020 to 12.56% in 2022 based on data from ePPBGM in 2022.